Do Muxarabi ao Brise-Soleil: a Arquitetura Brasileira Ajusta-se ao Clima - Bruna, Gilda Collet; Fretin, Dominique; Maia, Rechilene Mendonça; Szabo, Ladislao Pedro (Cadernos de Pós-Graduação em Arquitetura e Urbanismo, 2008)
Brazil’s territory displays a wide climatic diversification due to its large territory. Its major architectural problems are to deal with the intense solar radiation and humidity. The search for shading devices that allows cross ventilation is affected by technical solutions according to cultural features, as the Moresque ones that became a condition of good design. Islamic influence in Brazilian architecture left remarkable signs, and is a natural consequence of the historical process during the country growth. After centuries of Moorish occupation, the first Portuguese settlers brought Arab architecture’s culture to Brazil. This paper looks forward to contribute with an analysis of architectural solutions inherited from Islamic culture by Brazilians through Portuguese colonization. It shows how much these elements were and are still important for its own cultural identity. The paper also shows examples of contemporary architecture that uses mainly glasses associated to internal air conditioning systems. [Accepted for presentation at CSAAR – The Center for Study of Architecture in the Arab Region – 2007]